Analyzing the Impact of Energy Imports, Fuel Substitution and Technological Change on Real GDP: A Panel Data Study of ASEAN Countries - Torasa, Chonmapat; Mekhum, Witthaya (International Journal of Energy Economics and Policy, 2020)
The determinants of real GDP growth have been enticed the researchers and policy makers since the last century. This study aims to empirically analyze the role of efficient energy consumption in real GDP growth of ASEAN countries. For this purpose, study used energy import, fuel substitution, and technological change as independent variables to explain their impact on dependent variable such as real GDP growth. The panel data of eight ASEAN countries including Indonesia, Malaysia, Thailand, Singapore, Philippine, Vietnam, Cambodia, and Laos for the period of 1990-2016 are used in the study. In addition, two control variables, population growth and Nonrenewable energy consumption, are also incorporated in the model to check the robustness of results. In order to estimate the empirical model, panel cointegration technique is employed to check the long run relationship between variables. The findings of the study indicate that energy imports, fuel substitution, and technology change have positive contribution in the real GDP growth. From the findings it is anticipated that the study will provide useful policy guidelines to researchers and policy makers for planning and taking decision on future policies regarding energy consumption to further bolster the potential of real GDP of ASEAN countries. Keywords: Energy import, Fuel Substitution, Technological Change, Real GDP Growth JEL Classifications: P18, O14 DOI: https://doi.org/10.32479/ijeep.10453